2017
DOI: 10.1088/1367-2630/aa8029
|View full text |Cite
|
Sign up to set email alerts
|

Cluster size dependence of high-order harmonic generation

Abstract: We investigate high-order harmonic generation (HHG) from noble gas clusters in a supersonic gas jet. To identify the contribution of harmonic generation from clusters versus that from gas monomers, we measure the high-order harmonic output over a broad range of the total atomic number density in the jet (from 3×10 16 to 3×10 18cm 3 ) at two different reservoir temperatures (303 and 363 K). For the first time in the evaluation of the harmonic yield in such measurements, the variation of the liquid mass fracti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Whereas in Xe the cutoff frequency shows an increase with increasing backing pressure, this is not so clear in high-pressure Ar, as it shows saturation. A possible explanation is that the conditions for ideal phase matching may improve with increasing backing pressure, similarly to atoms [29]. Additionally, the monotonic increase for the largest clusters can partly be caused by increasing space charge of multiply ionized Xe (providing the largest clusters), in accordance with results of Ruf et al on multiply ionized Kr clusters [23].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Whereas in Xe the cutoff frequency shows an increase with increasing backing pressure, this is not so clear in high-pressure Ar, as it shows saturation. A possible explanation is that the conditions for ideal phase matching may improve with increasing backing pressure, similarly to atoms [29]. Additionally, the monotonic increase for the largest clusters can partly be caused by increasing space charge of multiply ionized Xe (providing the largest clusters), in accordance with results of Ruf et al on multiply ionized Kr clusters [23].…”
Section: Resultssupporting
confidence: 82%
“…However, a fundamental research question related to cluster-based HHG remained, namely whether the electron recombines to the parent ion in a cluster ("atom-to-itself" recombination) or recollision with neighbouring atoms is also possible resulting in "atom-to-neighbour recombination". This possible scenario was indirectly studied before [28,29] and further support for this hypothesis was provided by independent theory work [33][34][35][36]. It is also possible that harmonics come from a delocalized wavefunction over the whole cluster and to which they recombine coherently after tunneling out ("cluster-to-itself" recombination) [23].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Besides the grating qualification, the HHG source is verified in terms of the cut-off wavelength for further experiments. [41][42][43]…”
Section: High-harmonic-generation Sourcementioning
confidence: 99%
“…The interactions between short laser pulses and highdensity clusters has been studied extensively [8][9][10] due to the variety of applications from sources of soft x-ray or EUV emission [11][12][13] to high harmonic generation [14][15][16][17]. These articles found that differences in cluster density, cluster diameter, laser amplitude, or electric field gradient have a significant impact on the expansion of the cluster.…”
Section: Introductionmentioning
confidence: 99%